A dynamic simulation framework for CT perfusion in stroke assessment built from first principles. Issue 7 (9th May 2021) - Divel, Sarah E.; Christensen, Soren; Segars, William P.; Lansberg, Maarten G.; Pelc, Norbert J.
Abstract : Purpose: Physicians utilize cerebral perfusion maps (e.g., cerebral blood flow, cerebral blood volume, transit time) to prescribe the plan of care for stroke patients. Variability in scanning techniques and post‐processing software can result in differences between these perfusion maps. To determine which techniques are acceptable for clinical care, it is important to validate the accuracy and reproducibility of the perfusion maps. Validation using clinical data is challenging due to the lack of a gold standard to assess cerebral perfusion and the impracticality of scanning patients multiple times with different scanning techniques. In contrast, simulated data from a realistic digital phantom of the cerebral perfusion in acute stroke patients would enable studies to optimize and validate the scanning and post‐processing techniques. Methods: We describe a complete framework to simulate CT perfusion studies for stroke assessment. We begin by expanding the XCAT brain phantom to enable spatially varying contrast agent dynamics and incorporate a realistic model of the dynamics in the cerebral vasculature derived from first principles. A dynamic CT simulator utilizes the time–concentration curves to define the contrast agent concentration in the object at each time point and generates CT perfusion images compatible with commercially available post‐processing software. We also generate ground truth perfusion maps to which the maps generated by post‐processing software can be compared. Results: We demonstrate a dynamic CT perfusion study of a simulated patient with an ischemic stroke and the resulting perfusion maps generated by post‐processing software. We include a visual comparison between the computer‐generated perfusion maps and the ground truth perfusion maps. The framework is highly tunable; users can modify the perfusion properties (e.g., occlusion location, CBF, CBV, and MTT), scanner specifications (e.g., focal spot size and detector configuration), scanning protocol (e.g., kVp and mAs), and reconstruction parameters (e.g., slice thickness and reconstruction filter). Conclusions: This framework provides realistic test data with the underlying ground truth that enables a robust assessment of CT perfusion techniques and post‐processing methods for stroke assessment.